KONSEP PERUMUSAN DAN IMPLEMENTASI KEBIJAKAN PUBLIK DALAM MENUNJANG PEMBANGUNAN DAERAH - sari, ita purnama (Magister Administrasi Publik Program Pascasarjana Universitas Ngurah Rai, 2025)
Development is an effort carried out by government, society, and private sector continuously with aim of improving the welfare of the people, both materially and spiritually. Solve societal problems, public policies are created. The parties, especially the government, establish public policies that focus on meeting the needs and interests community. Indonesia recognizes the importance of public policy and its use. The purpose of this research is to understand concept formulating and implementing public policies in supporting regional development. The method used in this article is a literature study with data analysis techniques using filtering e-journals and other reliable articles. The research findings indicate that policy cycle offers several advantages, such as helping to simplify public policy formulation process, providing a great opportunity to conduct relevant public policy research systematically and analytically within the boundaries of the area, and serving as a benchmark to assess effectiveness and efficiency of a policy based on each stage.The non-implementation of a policy means that policy is not executed according to plan. Unsuccessful implementation usually occurs when a policy has been executed according to plan, but external conditions turn out to be very unfavorable, so the policy cannot achieve the desired impact or final outcome. Keywords : Public Policy, Formulation, Implementation